2016
DOI: 10.1097/md.0000000000004234
|View full text |Cite
|
Sign up to set email alerts
|

Using optical coherence tomography to assess the role of age and region in corneal epithelium and palisades of vogt

Abstract: Using spectral-domain optical coherence tomography (OCT) to observe the morphology and epithelial thickness (ET) of the palisades of Vogt (POV), and to evaluate the role of age and region on these structures.One hundred twelve eyes of 112 healthy subjects were enrolled and divided into 4 groups: A (0–19), B (20–39), C (40–59), and D (≥60 years old). RTvue-100 OCT was applied on the cornea and the limbus. The morphology of the subepithelial stroma underneath the epithelium of POV was classified into typical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…This constellation of features led to a decades‐long search for a bona fide LSC marker that would enable prospective LSC isolation for therapeutic applications. In 1971, Davanger and Evensen proposed that LSC reside in the palisades of Vogt (POV), a series of radially oriented fibrovascular ridges that are observed in the human limbus and can be detected by the optical coherence tomography . In 2005, based on histological examination of the human limbus, Dua et al reported the presence of limbal epithelial crypts (LEC) and proposed that they also harbor LSC .…”
Section: Limbal Stem Cell Identitymentioning
confidence: 99%
“…This constellation of features led to a decades‐long search for a bona fide LSC marker that would enable prospective LSC isolation for therapeutic applications. In 1971, Davanger and Evensen proposed that LSC reside in the palisades of Vogt (POV), a series of radially oriented fibrovascular ridges that are observed in the human limbus and can be detected by the optical coherence tomography . In 2005, based on histological examination of the human limbus, Dua et al reported the presence of limbal epithelial crypts (LEC) and proposed that they also harbor LSC .…”
Section: Limbal Stem Cell Identitymentioning
confidence: 99%
“…LSCs also exhibit heterogeneity [ 133 ]. Lin et al observed the morphology and measured the epithelial thickness of human limbal palisades of Vogt (POVs) by using the spectral-domain optical coherence tomography (SD-OCT) [ 134 ]. They found that the appearance of POVs and the thickness of limbal epithelium showed a big difference in different age groups and anatomical regions, suggesting that age and anatomic regions had significant effects on the microstructure of limbus.…”
Section: Difficulties In the Study Of Lsc-specific Biomarkersmentioning
confidence: 99%
“…A super luminescence diode emitted light with a 50 nm bandwidth was centred at 830 nm and had a scan speed of 26,000 axial scans per second with an axial resolution of 5 μ m. A corneal anterior module long adaptor lens was mounted on the probe and focused on the anterior segment part, including the IOL and PCO after pupil dilation. Patients were told to fixate straight ahead on the red light using the fellow eye [14]. Using a cornea cross line mode, images of the IOL and PCO on the vertical and horizontal meridians crossing the central cornea were taken, and then images were transferred to a personal computer for analysis using Image Pro Plus software 6.0.…”
Section: Methodsmentioning
confidence: 99%